Prioritising public health: a qualitative study of decision making to reduce health inequalities - O'Flaherty Martin; Moonan May; Taylor-Robinson David C; Lloyd-Williams Ffion; Orton Lois C; Capewell Simon (BMC, 2011)
Abstract Background The public health system in England is currently facing dramatic change. Renewed attention has recently been paid to the best approaches for tackling the health inequalities which remain entrenched within British society and across the globe. In order to consider the opportunities and challenges facing the new public health system in England, we explored the current experiences of those involved in decision making to reduce health inequalities, taking cardiovascular disease (CVD) as a case study. Methods We conducted an in-depth qualitative study employing 40 semi-structured interviews and three focus group discussions. Participants were public health policy makers and planners in CVD in the UK, including: Primary Care Trust and Local Authority staff (in various roles); General Practice commissioners; public health academics; consultant cardiologists; national guideline managers; members of guideline development groups, civil servants; and CVD third sector staff. Results The short term target- and outcome-led culture of the NHS and the drive to achieve "more for less", combined with the need to address public demand for acute services often lead to investment in "downstream" public health intervention, rather than the "upstream" approaches that are most effective at reducing inequalities. Despite most public health decision makers wishing to redress this imbalance, they felt constrained due to difficulties in partnership working and the over-riding influence of other stakeholders in decision making processes. The proposed public health reforms in England present an opportunity for public health to move away from the medical paradigm of the NHS. However, they also reveal a reluctance of central government to contribute to shifting social norms. Conclusions It is vital that the effectiveness and cost effectiveness of all new and existing policies and services affecting public health are measured in terms of their impact on the social determinants of health and health inequalities. Researchers have a vital role to play in providing the complex evidence required to compare different models of prevention and service delivery. Those working in public health must develop leadership to raise the profile of health inequalities as an issue that merits attention, resources and workforce capacity; and advocate for central government to play a key role in shifting social norms.